Presage, context, process and product: influencing variables in literature instruction in an ESL context - Fauziah Ahmad (Penerbit UKM, 2008)
The premise of this research is on the theoretical assumptions that teachers’ mental constructs can have significant pedagogical consequences (Clark and Peterson, 1986). It is necessary to describe the thinking and planning strategies so that one can fully understand classroom processes. National Institute of Education or NIE (1975a) cited in Clark and Peterson (1986) proposed a rationale for a program of research on teachers’ thoughts and processes. They assert that innovation in the contexts, practices and technology of teaching be mediated through the minds and motives of teachers. As teachers are able to understand and observe (thought processes) classroom behavior, student’s cognitive processes, students’ level of capability and ability and students’ inert interest and motivation, they can steer and adjust the classroom learning process according to the needs of the students. The success of any learning and teaching situation will depend a great deal on the teachers (Safiah Osman, 1992). Improving the ability of students to understand what they read is a never-ending process. Based on the theoretical premise and the consensus of views of other researchers, teachers’ thought processes have significant pedagogical consequences. The purpose of this research is to investigate systematically and empirically the teachers’ level of belief, background knowledge, attitude and perception towards literature and literature teaching, the extent of the influence of student factor and evaluation factor on literature teaching, the forms of teaching; student centered or teacher centered.